A Cross-Cultural Study in Germany, Russia, and China: Are Resilient and Social Supported Students Protected Against Depression, Anxiety, and Stress?. Issue 2 (April 2018) - Brailovskaia, Julia; Schönfeld, Pia; Zhang, Xiao Chi; Bieda, Angela; Kochetkov, Yakov; Margraf, Jürgen
This study cross-culturally investigated resilience and social support as possible protective factors for mental health. The values of depression, anxiety, and stress symptoms, resilience and social support were collected from German (N = 4433), Russian (N = 3774), and Chinese students (N = 4982). The samples were split (two-thirds vs. one-third) to cross-validate the results. In all samples, resilience and social support were significantly negatively associated with depression, anxiety, and stress symptoms. While in Germany those associations were stronger for social support, in Russia and in China stronger associations were found for resilience. Furthermore, in all samples, resilience was found to mediate the association between social support and the negative mental health variables significantly. In conclusion, resilience and social support are universal interrelated protective factors for mental health independently of historical, cultural, social, and geographical conditions of a country.